Influence of different root canal obturation materials in CBCT imaging: an in vitro evaluation. - Sales SALINEIRO, Fernanda Cristina; Kobayashi VELASCO, Solange; Mesquita BARROS, Fabiana; Pescinini SALZEDAS, Leda Maria; Oliveira SALES, Marcelo Augusto; Paraiso CAVALCANTI, Marcelo Gusmão (Dental Press Endodontics)
Objective: This study evaluated the influence of canal obturation materials in the production of cone beam computed tomography (CBCT) images artifact, by means of image density analysis and comparison between four materials in central incisors and monoradicular premolar teeth. Materials and Methods: The teeth were submitted to endodontic instrumentation and divided into 5 groups: one control group (no endodontic filling) and four test groups each one filled by a different endodontic sealer (PulpCanal Sealer, AHPlus, Sealer26 and BCSealer). After CBCT scanning, the images were assessed to determine grayscale variations in three root thirds (objective analysis). The second (subjective) analysis compared the control group with two of the test groups in a randomized process. Results: In the objective analysis, Sealer26 and BCSealer showed statistical difference for minimum values, in comparison with another sealers, for both anterior and posterior teeth. For maximum values, only control group differed statistically from test groups. When comparing premolars and central incisors grayscale values by ANOVA analysis, a statistically significant difference was found mainly for minimum values. At the subjective analysis, for both anterior and posterior teeth, PulpCanal Sealer was the filling most frequently appointed by the observers as the one that produced more artifact interference. Conclusion: Endodontic fillings at posterior teeth performed similar behavior. Only PulpCanal Sealer on apical third presented higher maximum values in relation to others groups, which could represent more white brands. For anterior teeth, BC Sealer performed higher minimum values in relation to other endodontic fillings, which could represent more dark bands.